Perancangan E-Katalog Promosi STMIK Triguna Dharma Dengan Metode User Centered Design Untuk Meningkatkan Layanan Kualitas Promosi Berbasis Web dan Mobile - Azlan, Azlan; Prayudha, Jaka (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Promotion is an activity to spread information with the aim that the information attracts the recipient's attention. The promotion strategy undertaken by STMIK Triguna Dhamra is to visit five schools in one day where one school spends an hour doing promotions, promotions are carried out for three months in the North Sumatra region. Promotion is done by asking permission from the school to make a presentation in class, the presentation is done using the brochure media that has been provided and distributed to students. Given the media used is a brochure which is a promotional media made of paper so that the quality of promotional services is mediocre or less attractive. To improve the quality of promotional services, a promotional e-catalog was designed. E-catalog is a digital version of the catalog and the catalog is a kind of brochure that contains product information and is equipped with images. The STMIK Triguna Dharma promotion e-catalog which is designed based on web and mobile, in addition to improving the quality of promotional services as well as saving costs of promotion, saving time on promotion and supporting government programs to face the industrial revolution 4.0, namely digital-based. Web-based and mobile e-catalogs are designed using the User Centered Design method where the e-catalog design is based on the needs of the promotion team and the order of research methods using the Research and Development method which is designing e-catalog products and testing the effectiveness